Characterization and Identification of Rice Germplasm Accessions Using Chemical Tests - CHANDU SINGH; SP JEEVAN KUMAR; SRIPATHY KV; SOMASUNDARAM G; UDAYA BHASKAR K; RAMESH KV; MADAN KUMAR; S RAJENDRA PRASAD (Seed Research, 2026)
Variety characterization and identification has become invariably significant for purity maintenance during seed production as well as for the varietal protection under plant variety protection. In the present study, utility of chemical tests for the purpose was evaluated in rice using 155 germplasm accessions. Based on phenol colour reactions, 155 germplasm accessions could be grouped into dark brown, brown, light brown, black and no colour reaction categories comprising of 34, 23, 33, 17 and 48 in each germplasm accession, respectively. Further, germplasm accessions under each category were subjected to modified phenol test that helped in further to differentiate or identification of the rice germplasm accessions. Similarly, sodium hydroxide test and potassium hydroxide test have grouped the germplasm accessions into 2 and 4 colour categories, respectively.